Junie B., first grader (at last!) - Park, Barbara (Park, Barbara. Junie B. Jones series, 2001)
Junie B. thinks first grade is a flop when her kindergarten friend Lucille prefers the company of twins Camille and Chenille and Junie B. needs glasses.